Effectiveness of Zinc Therapy with Zinc-Probiotic Combination Therapy on the Duration of Diarrhea During Hospitalization at Mawaddah Medika Hospital in October - December 2023 - Rosyid, Riga Abida; Arifin, Fabilla Faiz; Kristanto, Andika Yudha (Golden Ratio of Data in Summary, 2025)
Diarrhea is the third leading cause of death among children under five years old worldwide, with improper management both at home and in healthcare facilities being the primary cause. The World Health Organization (WHO) recommends zinc supplementation as a treatment for acute diarrhea, while probiotics, commonly used alongside fluid rehydration, are not yet included in WHO guidelines. This study used a single-blinded randomized Controlled Trial design to compare the effectiveness of zinc therapy versus a combination of zinc and probiotics on the duration of diarrhea during hospitalization at Mawaddah Medika Hospital. Children suffering from diarrhea who met specific inclusion and exclusion criteria were randomly assigned to two groups: one received zinc therapy, while the other received a combination of zinc and probiotics, along with standard treatments. The data were analyzed using the Mann-Whitney test. Eighty children participated in the study, with the majority (60.0%) aged 1-5 years, and 53.8% of the children were male. In the group receiving zinc therapy, diarrhea was approximately 8.54 hours shorter than in the zinc-probiotic combination group. However, the analysis revealed no significant difference in the duration of diarrhea between the two treatments (p > 0.05). Consequently, while no significant difference was found between zinc supplementation and zinc-probiotic combination therapy regarding the duration of diarrhea, further research is needed to explore the administration of these treatments in diarrhea patients.